Karyoevolution in Potamorhina (Cope, 1878) (Ostariophysi, Curimatidae): Using Repetitive DNA for the Elucidation of Genome Organization - Pinheiro, Vanessa Susan da Silva; Carvalho, Natália Dayane Moura; Carmo, Edson Júnior do; Schneider, Carlos Henrique; Feldberg, Eliana; Gross, Maria Claudia (Zebrafish, 2016)
Some families of Characiformes present the tendency toward stability of the karyotypic macrostructure as Curimatidae, which contains species with a 2n = 54 karyotype and metacentric and submetacentric chromosomes, however, some Potamorhina species contradict to this tendency. Some species of the central Amazon exhibit different diploid number and show intraspecific variation in the location of heterochromatin. By performing cytogenetic characterization by localization of heterochromatin and the nucleolus organizer region, as well as physical chromosome mapping using probes targeting 5S and 18S ribosomal DNA (rDNA), retroelement of Xiphophorus 1 (Rex1), Rex3, telomeres, and tropomyosin 1 (TPM1), we attempted to understand the evolutionary mechanisms involved in the differentiation of the Potamorhina species. The analyses showed that the heterochromatic regions of the examined species are distinct and transposable elements are involved in this evolutionary process, considering that the dynamic regions of the genome appear to include the terminal regions and particularly the heterochromatin-rich centromeric regions, which are involved in fission and fusion processes and promote the differentiation of chromosome pairs that bear ribosomal sites; these pairs were similar in the central Amazon species. Thus, we propose a phylogeny for this genus. © Copyright 2016, Mary Ann Liebert, Inc.
Keywords: Dna; Fish Protein; Ribosome Dna; Animals; Characiformes; Genetics; Genome; Interspersed Repeat; Karyotyping; Evolution, Molecular; Phylogeny; Species Difference; Telomere; Animal; Characiformes; Dna; Ribosomal Dna; Evolution, Molecular; Fish Proteins; Genome; Interspersed Repetitive Sequences; Karyotyping; Phylogeny; Species Specificity; Telomere